2021
DOI: 10.1002/aqc.3659
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge gaps and challenges for conservation of Mediterranean wetlands: Evidence from a comprehensive inventory and literature analysis for Sardinia

Abstract: Wetlands are some of the most important ecosystems on Earth. They play a key role in mitigating climate change‐related events and filtering polluted water, and provide habitats for a wide range of species. Despite their importance, and numerous regulations that support their conservation, wetlands continue to be destroyed. Recent reports have indicated a progressive decline in ecological character of remaining wetlands. This research reviews and extends the present status of wetland knowledge in Sardinia, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It seems that there is an asymmetry in the dedication of economic efforts toward this research located specifically in the Mediterranean Basin. The general increasing trend in publication rates, which raised particularly rapidly over the past two decades, has been also detected by Fois et al [54], who suggest that national and international initiatives, laws, conventions, and the establishment of conservation networks could have contributed to such a trend.…”
Section: Phylogeography and Conservation In Mtesmentioning
confidence: 60%
“…It seems that there is an asymmetry in the dedication of economic efforts toward this research located specifically in the Mediterranean Basin. The general increasing trend in publication rates, which raised particularly rapidly over the past two decades, has been also detected by Fois et al [54], who suggest that national and international initiatives, laws, conventions, and the establishment of conservation networks could have contributed to such a trend.…”
Section: Phylogeography and Conservation In Mtesmentioning
confidence: 60%
“…Previous studies have shown that bird specialisation on specific plant partners increases towards sites with relatively uncommon and extreme environmental conditions, such as forests above 3000 m asl [13] or small islands [50]. Similar specialised plant-bird interactions might be present in small and isolated wetlands where, according to the Italian island inventory [30,56], rare and specialist plant and bird species were more common than in large wetland systems, which are also often characterised by monodominant vegetation communities and relatively low niche variability. If considering that the extent of a site increases with the % of open water, our results are partially in contrast.…”
Section: Discussionmentioning
confidence: 88%
“…Much of the literature is focused on common, largeranged plant species that often offer utility to humans (Lughadha et al, 2020 and references therein). In addition to being innately vulnerable, many rare species and their functional traits and interactions within their environments are undescribed or poorly known causing their risk of extinction to be potentially underestimated (Pimm et al, 2014;Fois et al, 2021). A lack of upto-date research means that listing is prolonged due to insufficient data, and recovery efforts are often outlined and prioritized based on outdated datasets and information, which further perpetuates mismanagement and hinders plant protection and conservation (Estill and Cruzan, 1999;Le Roux et al, 2019;Molano-Flores and Coons, 2019).…”
Section: Introductionmentioning
confidence: 99%